4D printing of magnetic driving actuators for heat management - Haikal Bin Mansor (Nanyang Technological University, 2023)
4-dimensional (4D) printing is the next advancement after 3-dimensional (3D) printing. Instead of a rigid shape of the 3D printed that are not programmed to change shape, 4D printing is capable of printing a part that are programmed to change its shape with stimuli such as heat, moisture or magnets to name a few. This phenomenon can also be known as Shape Memory Effect and the material used for fabrication is Shape Memory Materials. This method can be applied to various industries such as robotics, medial and design.